2012 U.S. presidential election - Laidler, Paweł; Turek, Maciej (Kraków : Jagiellonian University Press, 2014)
During the 2012 election cycle, President Barack Obama was struggling for reelection, and former Massachusetts governor Mitt Romney was running as the first major-party candidate since Walter Mondale and the first Republican since Ronald Reagan to not hold public office at the time of his nomination. In this volume, twenty-six international scholars consider how these two different public figures steered toward the White House, discussing strategy, rhetoric, domestic and international policies, and campaign innovations.
Part one. Law, history, and politics of the U.S. Presidential elections -- The Constitution, the Electoral College, and the American concept of democracy : a view from Europe / Robert Podolnjak -- The elections of the first three American Presidents: how did Americans elect Washington, Adams and Jefferson? / Jolanta Daszyńska -- White House hostess, pet causes campaigner, convention speaker : evolution of position and role of American First Lady / Magdalena Paluszkiewicz-Misiaczek -- A study on the re-election chances of American Presidents: does the unemployment rate matter? / Marco Morini -- Conservative crime control v. Liberal due process and presidential elections / Paweł Laidler -- Presidential debate. Where is the question? / Magdalena Modrzejewska -- Part two. Domestic front -- The rhetorical currency of immigration reform / Donathan Brown -- Hispanics in the 2012 Presidential Elections / Anna Bartnik -- Discursive strategies in an era of economic crisis: Barack Obama, the American Dream and American Middle Class / Zinovia Lialiouti -- The White House in 2013: tax shelter from the storm? / Alix Meyer -- From the political wilderness to 'Civil War': the Republican Party during Obama's first term / Søren Christian Reimer -- God's chosen candidate: Mitt Romney and the role of religion in the 2012 Presidential campaign / Károly Pintér -- Barack Obama, religion, and the separation of church and state -- The renewed importance of intelligent design / John Bloom -- Part three. Media and culture in and on contemporary elections and politics -- U.S. Elections (Web) 2.0 : Can Romney outdo Obama in social media? / István Szokonya -- The synergy of microtargeting and social media unlocks the code of the American Presidential Election 2012 / Anna Severse -- A comparison of U.S. Presidential candidates' media image in Time and Newsweek / Bożena Pękala -- Paul Ryan and the Press / Maciej Turek -- Indecision 2012: cluster to the White House redux : U.S. Presidential Election, satire, and the new political media / Patrick Sadjak -- Cowboys go to Washington : Cowboy culture in Presidential politics / Jolanta Szymkowska-Bartyzel -- Part four. International context of 2012 Presidential Election -- The Obama Administration and human rights: between international PR and the American values / Spasimir Domaradzki, Piotr Józefczyk -- Mitt Romney's and Paul Ryan's rhetoric of anti-Europeanism and American exceptionalism / Alf Thomas Tønnessen -- To conduct or not to conduct the world (again): 2012 U.S. Presidential Candidate's dilemmas / Mateusz Bogdanowicz -- Europe in the politics of Barack Obama's administration / Dagmara Suberlak -- Europe is working in the United States: "Europe" and anti-Europeanism in the 2012 elections / Joost Baarssen -- The United States' foreign policy under Barack Obama's administration: an early assessment / Wojciech Michnik.
Includes bibliographical references.
Keywords: Obama, Barack; Romney, Mitt; Presidential candidates -- United States; Presidents -- United States -- Election -- 2012.; Political campaigns -- United States -- History -- 21st century; Obama, Barack; Romney, Mitt; Political campaigns; Presidential candidates; Presidents -- Election; United States; 2000-2099; History